[PP.29.21] LISINOPRIL EFFICIENCY IN OBESE HYPERTENSIVE MEN. (September 2016) - Stojanov, V.; Radivojevic, N.; Marjanovic, M.; Jakovljevic, B.; Lovic, D.
Abstract : Objective: The aim was to assess the effects of lisinopril combined with hydrochlorthiazide on blood pressure of hypertensive men with normal weight, overweight and obesity. Design and method: The study comprised 266 hypertensive men, aged 60.56 ± 11.50 years. All patients were treated with fixed combination of 20 mg lisinopril and 12.5 mg hydrochlorthiazide. Body mass index (BMI) was calculated from body weight divided by squared body height. Normal weight was defined as BMI from 18.5 to 24.9 kg/m 2, overweight as BMI from 25.0 to 29.9 kg/m 2 and obesity as BMI exceeding 30 kg/m 2 . Blood pressure (BP) was measured by an oscillometric device at the beginning of the study, and after three months of therapy. The differences between the groups were tested with one-way ANOVA. The differences from baseline values were tested with Student's t test for paired samples. Results: At the beginning of the study 39 men (14.7%) had normal weight, 163 men (61.3%) were overweight, and 64 (24.1%) were obese. All three groups of men had similar systolic (SBP) and diastolic pressures (DBP) at the beginning of the study as well as at the end of the study. Mean BMI remained stable during three months of antihypertensive therapy. Mean SBP for all patients at the beginning of the study was 162.52 ± 13.24 mmHg, mean DBP was 97.38 ± 8.62 mmHg. After three months of therapy, all men reduced their SBP significantly (mean decrease from baseline = 28.34 ± 13.45 mmHg), as well as their DBP (mean decrease from baseline = 15.04 ± 8.68 mmHg). The average decrease in SBP and DBP during therapy was similar among men with normal weight, overweight and obesity. Men with normal weight reduced their SBP by 30.19 ± 12.08 mmHg, in comparison to overweight men (27.70 ± 13.86 mmHg), and to obese men (28.35 ± 13.13 mmHg), but the difference was not statistically significant. Conclusions: Three-month therapy with lisinopril and hydrochlorthiazide is equally effective in hypertensive men with normal weight, overweight and obesity.